Penguatan Sektor Umkm Sebagai Strategi Menghadapi Mea 2015 - Prasetyoning Tyas, Ari Anggarani Winadi; Intan Safitri, Vita; Cahyadi, Lukman (Lembaga Penerbitan Unversitas Esa Unggul, 2014)
AbstractSome challenges MEA labor courts in Indonesia will only raise the unemployment rate itself, because it has no impact on improving the living standards of the people of Indonesia. If Indonesia is not ready, then the free flow of goods, services, investment, skilled labor and capital, seen as a threat rather than an opportunity. Another challenge is the horizontal chasm between countries with advanced economy class and are still intermediate and advanced. Vertical chasm between the liberal democratic state and still authoritarian. ASEAN Economic Community which was formed with a mission to make the economy in ASEAN for the better and be able to compete with countries - countries whose economies are more advanced than the current condition of the ASEAN countries. In addition, the realization of the ASEAN Community in which there is AEC, can make ASEAN into a more strategic position in the international arena, we expect the realization of the ASEAN economic community is able to open the eyes of all parties, so that there is a dialogue between sectors that will also be complementary among stakeholders in the State sector of the economy of ASEAN countries. Indonesia challenges ahead realize meaningful change to the lives of everyday people. This opportunity is open, if not immediately used will be left behind, because the process is also followed the motion of other countries and it continues to unfold.Keywords: SMEs, Strategy, ASEAN AbstrakBeberapa tantangan MEA seperti lapangan tenaga kerja yang ada di Indonesia hanya akan menaikkan angka pengangguran itu sendiri, karena tidak berdampak pada peningkatan taraf hidup masyarakat Indonesia. Bila Indonesia tidak siap, maka aliran bebas barang, jasa, investasi, tenaga kerja terampil dan modal, terlihat sebagai ancaman daripada peluang. Tantangan lainnya adalah jurang horizontal antara negara dengan kelas ekonomi maju dan yang masih menengah dan maju. Jurang vertikal antara negara yang demokratis liberal dan masih otoriter. ASEAN Economic Community yang dibentuk dengan misi menjadikan perekonomian di ASEAN menjadi lebih baik serta mampu bersaing dengan Negara - negara yang perekonomiannya lebih maju dibandingkan dengan kondisi Negara ASEAN saat ini. Selain itu juga dengan terwujudnya ASEAN Community dimana di dalamnya terdapat AEC, dapat menjadikan posisi ASEAN menjadi lebih strategis di kancah Internasional, kita mengharapkan dengan terwujudnya komunitas masyarakat ekonomi ASEAN ini dapat membuka mata semua pihak, sehingga terjadi suatu dialog antar sektor yang nantinya juga saling melengkapi diantara para stakeholder sektor ekonomi di Negara negara ASEAN. Tantangan Indonesia kedepan mewujudkan perubahan yang berarti bagi kehidupan keseharian masyarakatnya. Peluang yang sudah terbuka ini, kalau tidak segera dimanfaatkan akan tertinggal, karena proses ini juga diikuti gerak negara lain dan hal itu terus bergulir. Kata kunci: UMKM, Strategi, ASEAN